2017
DOI: 10.1177/1076029617731624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thromboelastometry in Sepsis in Correlation With Bleeding During Invasive Procedures

Abstract: Prolongation of prothrombin time (PT) is often encountered in patients with sepsis. On the other hand, thromboelastometry as a global coagulation test might yield normal results. The aim of our study was to evaluate whether prolonged PT in the presence of normal thromboelastometry parameters is associated with severe bleeding in patients with sepsis undergoing invasive procedures. In patients with sepsis undergoing low-risk bleeding invasive procedures (central venous catheter placement, dialysis catheter inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…15 Recently, we published results of study done in adult patients which supported the findings of Müller et al and ROTEM seems to be providing more light into this phenomenon and coagulation process of critically ill adult patients. 17 No analogous study was performed in pediatric patients and our findings suggest that the results in the pediatric population might be very similar, but more studies are needed. Fresh frozen plasma is often used in pediatric patients in daily practice to correct prolonged PT/ aPTT, although it is well known that prophylactic plasma is not effective in the correction of INR and, even worse, it can be harmful for patients and is associated with increased morbidity and mortality of patients.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…15 Recently, we published results of study done in adult patients which supported the findings of Müller et al and ROTEM seems to be providing more light into this phenomenon and coagulation process of critically ill adult patients. 17 No analogous study was performed in pediatric patients and our findings suggest that the results in the pediatric population might be very similar, but more studies are needed. Fresh frozen plasma is often used in pediatric patients in daily practice to correct prolonged PT/ aPTT, although it is well known that prophylactic plasma is not effective in the correction of INR and, even worse, it can be harmful for patients and is associated with increased morbidity and mortality of patients.…”
Section: Discussionmentioning
confidence: 71%
“…and the methodology was analogous to our previous study done in adults patients. 17 Patients with prolonged aPTT represented by aPTT ratio (aPTT-R) or PT represented by international normalized ratio (INR) and PT ratio (PT-R) and with normal ROTEM tests-internal thromboelastometry (INTEM) (assessing internal pathway of coagulation, contains activator of intrinsic pathway) and external thromboelastometry (EXTEM) (assessing external pathway of coagulation, contains activator of extrinsic pathway)-were included in the study. In case of normal ROTEM results, they were not administered fresh frozen plasma preventively before intervention despite prolonged aPTT or PT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50][51][52] It has been shown that in septic patients with prolonged prothrombin time but normal or hypercoagulable parameters of viscoelastometric testing, invasive procedures are not associated with an increased bleeding risk. 53,54 This is also reflected by the discordance that has been observed between international normalized ratio and TEG R times in previous studies. 55 Also, both hyperor hypofibrinolysis can be detected by viscoelastometric testing in trauma patients and patients with sepsis, DIC, or liver disease.…”
Section: Assessment Of Prothrombotic Abnormalities and Complex Coagulmentioning
confidence: 77%
“…Therefore, in case of normal ROTEM, we did not see any bleeding complication during small surgical procedures or afterwards despite prolonged PT/aPTT or low platelets count [4]. The authors also demonstrated no bleeding complications in septic patients [13]. …”
Section: Discussionmentioning
confidence: 99%